1999
DOI: 10.1108/13673279910288707
|View full text |Cite
|
Sign up to set email alerts
|

Organisational factors and knowledge management within large marketing departments: an empirical study

Abstract: One hundred and seventy‐nine heads of sales or direct marketing departments in large UK companies across five industry sectors completed mail questionnaires concerning the knowledge management (KM) practices employed by their firms. The extents of the KM systems operating within sample enterprises were analysed with respect to each company’s use of teamwork, level of bureaucracy and centralisation of decision making, innovativeness, and ability to cope with change. Respondents’ views on the contributions of KM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 47 publications
5
148
0
10
Order By: Relevance
“…Researchers have confirmed that face-to-face meetings are the key driver for knowledge transfer and crystallisation of new ideas, and are the best method for the manifestation of alternative opinion (Swan et al, 1999;Bennett & Gabriel, 1999). The finding from this study confirms that complex information is transmitted face-to-face in an office.…”
Section: We Went For a Two Weeks Training Together I Guess I Know Hesupporting
confidence: 76%
“…Researchers have confirmed that face-to-face meetings are the key driver for knowledge transfer and crystallisation of new ideas, and are the best method for the manifestation of alternative opinion (Swan et al, 1999;Bennett & Gabriel, 1999). The finding from this study confirms that complex information is transmitted face-to-face in an office.…”
Section: We Went For a Two Weeks Training Together I Guess I Know Hesupporting
confidence: 76%
“…Researchers have confirmed that face-to-face meetings are the key driver for knowledge transfer and crystallisation of new ideas, and are the best method for the manifestation of alternative opinion (Swan et al, 1999;Bennett & Gabriel, 1999). The finding from this study confirms that complex information is transmitted face-to-face in an office.…”
Section: We Went For a Two Weeks Training Together I Guess I Know Hesupporting
confidence: 78%
“…Indeed, the changing organisational environment as a result of business having to deal with complexities such as sustainability imperatives has driven interest in organisational learning and knowledge management, with Bennet and Gabriel (1999) asserting that customer knowledge is one of the most important knowledge bases for an organisation. Accordingly, there is increasing interest in the potential of value cocreation to enhance innovation and business performance, whereby market intelligence is embedded in dynamic co-creation processes that involve customers as partners rather than subjects (Rowley, Kupiec-Teahan & Leeming, 2007).…”
Section: The Case For Co-creation Towards Sustainable Consumptionmentioning
confidence: 99%
“…Kristensson, Gustafsson and Archer (2004) have examined the benefits of involving users in suggesting new product ideas, finding that ordinary users create significantly more original and valuable ideas than professional developers. Hsieh and Chen (2005) showed that new product development can be enhanced by interacting with users, and capitalising on user-knowledge management competencies, supporting the assertion by Bennet and Gabriel (1999) of the importance of customer knowledge for an organisation. Matthing, Sanden and Edvardsson (2004) suggest that the value of customer involvement in new service development resides in the opportunity to facilitate proactive learning about the customer, and to understand and anticipate latent customer needs.…”
Section: An Introduction To Value Co-creationmentioning
confidence: 99%